Toxoplasma gondii protease inhibitor-1 (TgPI-1) is a novel vaccine candidate against toxoplasmosis - Cuppari, Anahi Fernandez (2008)
Fil: Cuppari, Anahi Fernandez. Laboratorio de Inmunología, Centro de Salud y Medio Ambiente, E.C.y T., Universidad de Gral. San Martín, Provincia de Buenos Aires; Argentina.